Blockchain tax havens and financial secrecy: Liberland as a case study - Sebastian Rivero Silva (Atlantic Review of Economics (ARoEc), 2025)
This article delves into the transition from traditional tax havens to a new generation of digital jurisdictions powered by blockchain technology. It examines how blockchain wallets and decentralized exchanges are redefining financial sovereignty by offering anonymity, asset protection, and economic delocalization in response to increasing global regulatory scrutiny. While these tools revolutionize sovereign approaches to financial management, they also pose significant risks to nation-states, such as facilitating money laundering, asset concealment, and ultimately, tax evasion. Through the case study of Liberland, a self-proclaimed micronation aspiring to be a "blockchain tax haven," the article reveals the tensions between libertarian utopian ideals and the practical limitations encountered in reality. Despite its ambitious vision, Liberland lacks the legal and economic infrastructure necessary to fulfill its promises, underscoring the challenges of transforming libertarian ideals into functional realities. The analysis suggests that the inefficient use of blockchain technology to achieve financial sovereignty is closely tied to Liberland's failure to realize its libertarian aspirations. Finally, the article highlights the transformative potential of blockchain-based tax havens. By combining private justice through arbitration, digital autonomy in corporate structures, and financial decentralization enabled by blockchain, true virtual jurisdictions could emerge. These jurisdictions hold particular appeal for individuals and entities seeking greater autonomy and financial protection from state intervention. – – El presente artículo explora la transición de los paraísos fiscales tradicionales hacia una nueva generación de jurisdicciones digitales impulsadas por la tecnología blockchain. Se analiza cómo las billeteras blockchain y los exchanges descentralizados están redefiniendo la soberanía financiera, ofreciendo anonimato, protección de activos y deslocalización económica frente a la creciente presión regulatoria global. Estas herramientas, aunque revolucionarias en su nuevo enfoque soberanista, también plantean riesgos para los Estados, como facilitar el lavado de dinero, el ocultamiento de patrimonio y en definitiva, la evasión fiscal. A través del caso de Liberland, una micronación autoproclamada que aspira a ser un "crypto paraíso fiscal", se revelan las tensiones entre la utopía libertaria y las limitaciones prácticas surgidas en la realidad. Liberland, a pesar de sus ambiciones, carece de infraestructura jurídica y económica para cumplir sus promesas, evidenciando los retos de convertir ideales libertarios en realidades funcionales. Se plantea que un uso ineficiente de la tecnología blockchain para obtener soberanía financiera está íntimamente relacionado con la falta de éxito de Liberland en sus pretensiones liberrtarias. Finalmente, se destaca el potencial transformador de los "crypto paraísos fiscales". Mediante una combinación de justicia privada basada en arbitraje, autonomía digital en la creación de sociedades de capital y descentralización financiera basada en el blockchain, se podrían constituir verdaderas jurisdicciones virtuales, especialmente útiles en la búsqueda de una mayor autonomía y protección financiera frente al Estado.
Keywords: H26; H71; J52; 330; Tax haven; Financial secrecy; Blockchain; Virtual jurisdiction; Liberland; Exchanges